A new species of the Goblin Spider genus Predatoroonops Brescovit, Rheims & Ott 2012 (Araneae, Dysderoidea: Oonopidae), with new records for the genus - Pereira, Maria Paula; Labarque, Facundo Martín (Zootaxa, 2021)
The family Oonopidae Simon, 1890 is composed of tiny spiders between 0.5 and 4mm (Baehr et al. 2012) that are distributed all over the world (Platnick et al. 2020; World Spider Catalog 2021). They occupy diverse habitats, mainly in tropical and subtropical regions (Platnick et al. 2020), generally associated with the soil and litter fauna (Ranasinghe & Benjamin 2018). Oonopidae is among the eight most diverse spider families with 114 genera and 1872 species (World Spider Catalog 2021). Most of this diversity was discovered after 2006, as a result of the Planetary Biodiversity Inventory (PBI) project: Goblin Spider (Platnick et al. 2012). Recent molecular phylogenetic analyses recovered Oonopidae as monophyletic (Wheeler et al. 2017), hypothesis supported by the presence of a synapomorphic pair of completely fused testicles (Burger & Michalik 2010). Brazil has a great diversity of Oonopidae (e.g., Brescovit et al. 2012a; Platnick et al. 2013; Feitosa et al. 2017), including the genus Predatoroonops Brescovit, Rheims & Ott 2012, endemic to the Atlantic Forest, that includes 17 species (World Spider Catalog 2021). The genus can be recognized by the male chelicerae frontally modified, with one or two pairs of distally sclerotized, and sometimes branched, apophyses, and by the pars cephalica dorsally squared (Brescovit et al. 2012b). In this paper, we describe a new species of the genus, based on a male specimen from the State of Minas Gerais: Predatoroonops stani sp. nov.. Also, we give new records for Predatoroonops yautja Brescovit, Rheims & Santos, 2012 from the same state and a distribution map with all the records of Predatoroonops along the Atlantic Forest.